The National Frame : Art and State Violence in Turkey and Germany - Karaca, Banu (Fordham University Press, 2021)
The National Frame rethinks the politics of art by focusing on the role of art in state governance. It argues that artistic practices, arts patronage and sponsorship, collecting and curating art, and the modalities of censorship, continue to be refracted through the conceptual lens of the nation-state, despite the globalization of the arts.
Keywords: Art and state -- Turkey -- History.; Art and state -- Germany -- History.; Politics and culture -- Turkey.; Politics and culture -- Germany.; Arts -- Political aspects -- Turkey.; Arts -- Political aspects -- Germany.; Art -- Politique gouvernementale -- Allemagne -- Histoire.; Politique et culture -- Allemagne.; Arts -- Aspect politique -- Allemagne.; ART -- Museum Studies.; Art and state; Arts -- Political aspects; Politics and culture; Germany; Turkey; East/West binary.; anthropology of art.; art world.; comparison.; cultural memory.; cultural policy.; dispossession.; modernity.; nationalism.; state violence.; History